Respuesta :

gmany

Answer:

[tex]\large\boxed{(9x^2y^3)(12x^{-3}y^5)(2xy)=216y^9}\to\boxed{B.}[/tex]

Step-by-step explanation:

[tex](9x^2y^3)(12x^{-3}y^5)(2xy)=(9\cdot12\cdot2)(x^2x^{-3}x)(y^3y^5y)\\\\\text{Use}\ a^n\cdot a^m=a^{n+m}\\\\=216x^{2+(-3)+1}y^{3+5+1}=216x^0y^9\\\\\text{Use}\ a^0=1\ \text{for any value of}\ a\ \text{except 0}\\\\=216y^9[/tex]

Answer:

[tex]=216y^9[/tex]

Step-by-step explanation:

the expression is:

[tex](9x^2y^3)(12x^{-3}y^5)(2xy)[/tex]

the first step is to multiply all the coefficients:

[tex]9*12*2=216[/tex]

and as for the variables, to multiply them we must add the exponents, that is, the result for x will be:

[tex]x^{2-3+1}=x^0=1[/tex]

so there will be no x in our result.

adding the exponents for the y variable:

[tex]y^{3+5+1}=y^9[/tex]

The result is the multiplied coefficients and the variables after we add the exponents they in the original expression:

[tex](9x^2y^3)(12x^{-3}y^5)(2xy)[/tex][tex]=216y^9[/tex]

which is option B

ACCESS MORE